2011
DOI: 10.2478/s11536-010-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of thyroid function after hemithyroidectomy

Abstract: AbstractIdentify criteria and create a risk scoring system to predict hypothyroidism after hemithyroidectomy. We have retrospectively studied 216 cases of patients with goiter who had undergone hemithyroidectomy from January 2002 to December 2007 at Vilnius University Hospital Santariškių Klinikos. Patients were divided into two groups according to their thyroid function after hemithyroidectomy: 168 (77.8%) patients’ thyroid function was normal (group A), 48 (22.2%) patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the current study, we also confirmed previous studies that reported the cutoff value of preoperative serum TSH level as 1.7 mIU/L by receiver operating characteristic curve analysis. The cutoff values in previous studies ranged between 1.4 and 2.5 mIU/L (10,11,14,29). Intriguingly, right-side lobectomy associated with postoperative hypothyroidism in the current study might be related to the residual thyroid volume, given that right thyroid lobe is usually bigger than left lobe (30); however, this conclusion is limited as the volume of the resected lobe was not measured.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the current study, we also confirmed previous studies that reported the cutoff value of preoperative serum TSH level as 1.7 mIU/L by receiver operating characteristic curve analysis. The cutoff values in previous studies ranged between 1.4 and 2.5 mIU/L (10,11,14,29). Intriguingly, right-side lobectomy associated with postoperative hypothyroidism in the current study might be related to the residual thyroid volume, given that right thyroid lobe is usually bigger than left lobe (30); however, this conclusion is limited as the volume of the resected lobe was not measured.…”
Section: Discussionmentioning
confidence: 57%
“…However, recent evidence has questioned the efficacy of levothyroxine supplementation because of possible adverse effects of thyroid-stimulating hormone (TSH) suppression in patients with low-risk DTC, leading to its decreased utilization (13)(14)(15). Therefore, it is critical to have a better understanding of the incidence and causes of postoperative hypothyroidism and appropriate strategies for its surveillance in patients undergoing lobectomy for lowrisk DTC.…”
mentioning
confidence: 99%
“…This issue has led to our interest in establishing precise and simple criteria for predicting residual thyroid function preoperatively. Recently, our retrospective pilot study has identified three risk factors for the PH after hemithyroidectomy: preoperative TSH level, age, and ratio of the remaining thyroid weight to the patient's weight [ 8 ]. Our current aim was to perform a prospective study with expanded list of potential risk factors and to develop a scoring system to grade the risk of PH.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the age is a risk factor. 1,4,5 But more studies showed that there is no relation between age and the risk of hypothyroidism in hemithyroidectomy. [1][2][3][6][7][8][9] Female gender noticed to be a risk factor developing hypothyroidism in hemithyroidectomy.…”
Section: Discussionmentioning
confidence: 99%